The impact of university-based incubation support on the innovation strategy of academic spin-offs. (April 2016) - Soetanto, Danny; Jack, Sarah
Abstract: This paper develops understanding about how incubation support and innovation strategy can determine the performance of academic spin-offs. Using a sample of spin-offs from the United Kingdom, the Netherlands and Norway, we analyse the potential moderating effect of incubation support (networking and entrepreneurial support) on innovation strategy effectiveness. The empirical results demonstrate: (1) a technology and market exploitation strategy has a stronger and more positive effect on the performance of spin-offs than a technology and market exploration strategy. In relation to an ambidextrous technology and market exploration and exploitation strategy, a market growth strategy (combining technology exploitation and market exploration) has a positive effect on performance while a product development strategy (combining technology exploration and market exploitation) has little effect on performance; (2) incubation support in the form of networking and entrepreneurial support has a positive effect on the performance of spin-offs; (3) networking support moderates the relationship between an exploitation strategy and spin-off performance while entrepreneurial support moderates the relationship between a market growth strategy and spin-off performance. By examining the interactions between types of innovation strategies and incubation support, this study provides a more refined understanding of the strategy selected by spin-offs. In doing so, it offers new insights about the role of incubator support in enhancing the effect of strategy on performance.